2006
DOI: 10.1128/aem.00201-06
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Organization and Regulation of Magnetosome Operons in Magnetospirillum gryphiswaldense

Abstract: Genes involved in magnetite biomineralization are clustered within the genomic magnetosome island of Magnetospirillum gryphiswaldense. Their transcriptional organization and regulation were studied by several approaches. Cotranscription of genes within the mamAB, mamDC, and mms clusters was demonstrated by reverse transcription-PCR (RT-PCR) of intergenic regions, indicating the presence of long polycistronic transcripts extending over more than 16 kb. The transcription start points of the mamAB, mamDC, and mms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 39 publications
5
66
0
6
Order By: Relevance
“…These genes not only show similar sequence homologies to others of their type, the organization of these genes show similar short intergenic distances between them and an identical direction of transcription, providing evidence that they are organized as an operon as described for other MTB (Schü bbe et al, 2006). The presence of mam genes and their organization in the Nitrospirae and various classes of the Proteobacteria strongly supports a monophyletic origin for magnetite-based magnetotaxis.…”
Section: Discussionsupporting
confidence: 53%
“…These genes not only show similar sequence homologies to others of their type, the organization of these genes show similar short intergenic distances between them and an identical direction of transcription, providing evidence that they are organized as an operon as described for other MTB (Schü bbe et al, 2006). The presence of mam genes and their organization in the Nitrospirae and various classes of the Proteobacteria strongly supports a monophyletic origin for magnetite-based magnetotaxis.…”
Section: Discussionsupporting
confidence: 53%
“…The transcription levels of several genes, which varied in response to the iron and oxygen concentrations in the MSR-1 strain, were analysed by reverse transcriptase-polymerase chain reaction (RT-PCR) and microarray. Although results from the two methods were not consistent in certain areas, seven genes (mgI458, mgI460, mamG, mamD, mamM, mamA and mamB) were determined to be downregulated under the iron-limiting condition (less than 1 mM iron; Schübbe et al 2006). Seven other genes (mgI458, mgI460, mamD, mamH, mamK, mamM and mamA) were downregulated under the aerobic (10 kPa O 2 ) condition in both the methods.…”
Section: Gene Expression Analysis Of Iron-inducible Genesmentioning
confidence: 85%
“…It has been shown that the regions between and flanking the identified magnetosome operons have no functional relevance for magnetosome biosynthesis in M. gryphiswaldense and M. magneticum (7,18). In M. gryphiswaldense, the mms6, mamGFDC, mamAB, and mamXY operons are transcribed as single polycistronic messengers under the control of the P mms6 , P mamDC , P mamH , and P mamXY promoters, respectively (19,20). A mutant with a deletion of mamGFDC op , encoding the most abundant magnetosome proteins, retained the ability to form magnetic, although smaller and less regular, magnetosomes, while plasmidal overexpression of the entire mamGFDC operon yielded magnetite particles even larger than those produced by the wild type (WT) (21).…”
mentioning
confidence: 99%